Transport and Logistics in Djibouti : Contribution to Job Creation and Economic Diversification - World Bank (Washington, DC, 2013)
The objective of this policy note is: (i) assessing the current situation of the transport and logistics sector in Djibouti, in particular regarding employment; (ii) examining the potential of the sector for creating jobs and generating new activities; and (iii) analyzing the constraints and making recommendations to alleviate. The note is divided into three chapters: (1) a diagnosis of transport and logistics; (2) opportunities and strategic priorities for the future; and (3) a suggested action plan. This policy note deals with transport and logistics and provides key input to the Djibouti New Growth Model study. The note relies on the findings of the World Bank mission that visited Djibouti in January 2012 to collect data and interview various representatives of the public and private sectors, as well as on a literature review. The note concludes that transport and logistics have a relatively limited potential for reducing unemployment since port activities are capital-intensive; the trucking industry serving the corridor to Ethiopia is totally dominated by Ethiopians; and the ongoing improvement of the supply chain s efficiency tends to cut jobs for a given volume of trade.